2015
DOI: 10.1016/j.bbr.2015.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume reduction in female but not male recent abstinent methamphetamine users

Abstract: Background and Aims Growing evidence suggests abnormalities in brain morphology including hippocampal structure in patients with methamphetamine (MA) dependence. Yet little is known about the possible gender difference. This study was performed to examine hippocampal volume in abstinent male and female MA users, and to further explore its relationship with cognitive function. Methods 27 abstinent MA users (19 males and 8 females) with average 5.75 months of duration and 29 healthy controls (19 males and 10 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Female METH users currently in abstinence had reductions in hippocampal volumes compared to control females, whereas no difference was observed between METH-abusing and control male subjects (Du et al, 2015). Furthermore, female METH users had significantly lower phosphocreatine levels in the frontal lobe compared to male METH users (Sung et al, 2013).…”
Section: 0 Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Female METH users currently in abstinence had reductions in hippocampal volumes compared to control females, whereas no difference was observed between METH-abusing and control male subjects (Du et al, 2015). Furthermore, female METH users had significantly lower phosphocreatine levels in the frontal lobe compared to male METH users (Sung et al, 2013).…”
Section: 0 Introductionmentioning
confidence: 80%
“…Of clinical relevance, male recently abstinent human psychostimulant users (cocaine or METH users) had higher serum BDNF levels than females when the number of abstinence days was controlled for (Hilburn et al, 2011). Further, recently abstinent female METH users but not males had decreased hippocampal volumes compared to sex-matched controls (Du et al, 2015). Perhaps prolonged use of METH coupled with a lack of changes in BDNF may contribute to lower hippocampal volumes.…”
Section: 0 Discussionmentioning
confidence: 99%
“…For example, gender-specific histological alterations were observed in the hippocampal GABAergic neuronal network, and the level of methamphetamine-induced DA release in the nucleus accumbens was also reported to vary according to gender (18). Taking these findings together with ours, the actions of DISC1 in each brain region might be gender-dependent, and a deficiency of DISC1 could accentuate gender-dependent sensitivity to psychostimulants (20).…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies in rodents have found sex differences in methamphetamine pharmacokinetics (Milesi-Halle et al, 2015, Rambousek et al, 2014), methamphetamine-induced plasma corticosterone levels (Zuloaga et al, 2014), methamphetamine-related neurotoxicity (Bourque et al, 2011), and methamphetamine self-administration with female rats acquiring methamphetamine self-administration faster, self-administering more methamphetamine, and exhibiting higher rates of methamphetamine reinstatement than male rats (Roth and Carroll, 2004, Ruda-Kucerova et al, 2015). In humans, female methamphetamine users have a higher risk of Parkinson's disease (Curtin et al, 2015), greater reductions in hippocampal volume (Du et al, 2015) and higher prevalence of physiologic dependence symptoms (Wu et al, 2009) compared to male methamphetamine users and these biological or other psycho-social differences may have a greater influence on methamphetamine use frequency in females than the SNPs examined here. Interestingly, amphetamine-induced CREB-mediated transcription differs dramatically between male and female mice in the nucleus accumbens, ventral tegmental area, amygdala, and locus coeruleus with greater CREB-meditated gene transcription following amphetamine in females (Shaw-Lutchman et al, 2003) suggesting that the significant association between rs7591784 and methamphetamine-related phenotypes observed in our study in males but not females may be due to underlying sexual dimorphism in the CREB signaling pathway.…”
Section: Discussionmentioning
confidence: 86%